Verso un’analisi socio-giuridica delle questioni ambientali in Europa (Società e diritti, 2022)
The author draws attention to the environmental issues of European law as well as the importance of Sociology of law. Environmental policies of the European Community are implemented in the member states, but the implementation of environmental objectives and the corresponding administrative measures imply difficult social issues. Indeed, there is no doubt that environmental issues are the core of current public debate, around which national and supranational strategies and practices are also organized. Alongside a historical and institutional reconstruction, the discussion specifically analyzes the sociological aspects of "environmental damage." In this perspective, the author has taken into account the fact that disasters are increasingly regarded as partially man-made rather than as purely natural events.